Healthy-minded religious phenomenon in shalawatan: a study on the three majelis shalawat in Java - Sekar Ayu Aryani (IAIN Salatiga, 2017)
As a movement, majelis shalawat becomes religious phenomenon that recently flourish in Indonesia, particularly Java. It emerges as urban spirituality like majelis dzikir that previously popular among people. However majelis shalawat is dissimilar with majelis dzikir due to its characters are not sadness, sorrow, and crying; it prefer to express happiness, cheerful, and enjoying religion. These characters indicate a Healthy-minded religious phenomenon, a term which is came originally from William James and popularized by W.H.Clark. Among many majelis shalawat groups ini Indonesia, the three most famous and biggest are Majelis Shalawat Habib Syech (Surakarta), Habib Luthfi (Pekalongan), and Maiyah Cak Nun (Yogyakarta). This research explores characteristics of majelis shalawat that indicate healthy-mindedness. Furthermore, it also discovers various motivations that lead people (jamaah) to follow the majelis shalawat. Conducting qualitative method and Psychology of Religion approach, and employing interview and observation as method for data gathering, it results several findings. First, as a religious activity, shalawatan reallydepends on the role of its charismatic leader. The charisma of Habib Luthfi, Habib Syech, and Cak Nun is the main attractive factor for jamaah to come. It ;